(untitled) (Journal of Science Foundation, 2013)
The present investigation is a humble attempt to explore fishing techniques of the River Baral from November 2010 to May 2011. Different fish capture methods, fishing gears and crafts that were usually used in the study area have been provided. Hand fishing, cloth fishing, bait fishing and fishing by dewatering were also observed. Causes of habitat degradation and changes of natural habitat and declination of fishes were also observed. Some problems of the fishing community of the study area were also identified. A few policy recommendations have been given in the concluding chapter which may have some positive implication on the life and living of the fishermen in Bangladesh in general and the Baral basin in particular. DOI: http://dx.doi.org/10.3329/jsf.v9i1-2.14654 J. Sci. Foundation, 9(1&2): 115-124, June-December 2011